The Effect of Crossword Puzzle Game Teaching Media to the Vocabulary Mastery of Seventh Grade Students of SMP Negeri 2 Siantar - Siahaan, Sanggam; Siahaan, Mungkap Mangapul; Tamba, Dian Winda (The Future of Education Journal, 2024)
This research investigates the impact of crossword puzzle game teaching media on the vocabulary mastery of seventh-grade students at SMP Negeri 2 Siantar. It utilizes Case's theory for crossword puzzles and Amin & Sumendap's theory for scramble games. Employing a quantitative research method with a quasi-experimental design, the study focused on seventh-grade students during the 2024/2025 academic year. The experimental group was taught using crossword puzzles, while the control group used scramble games. The results revealed that the experimental group had a higher mean score, with a pre-test score of 56.5 and a post-test score of 74.33. In comparison, the control group's pre-test mean was 51.83, which increased to 64.33 in the post-test. A t-test analysis showed a t-test value of 2.35, which is greater than the critical value of 1.67. Consequently, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected, indicating that the crossword puzzle game had a more significant effect on vocabulary mastery than the scramble game for seventh-grade students at SMP Negeri 2 Siantar.